Bactericidal effect of silver nanoparticles against the propagation of Clavibacter michiganensis infection in Lycopersicon esculentum Mill. - Rivas Caceres, Raymundo Rene (2018)
This study explored the use of silver nanoparticle as a bactericidal against the propagation of Clavibacter michiganensis onto tomatoes (Lycopersicon esculentum Mill). In Mexico, tomato production covers about 73% of the total vegetable production but it is affected by outbreak of bacteria canker caused by Clavibacter michiganensis subspecies michiganensis (Cmm). Silver ions possess inhibitor properties, bactericides and high specter antimicrobials. In this study, 6 groups of culture were prepared using 6 different petri dishes where silver nanoparticles of varying concentrations (120, 84, 48, 24, 12 and 0 μg) were added. Furthermore, each group was observed for 20 min, 1, 2, 12 and 24 h. The optimum concentration is 84 μg, which shows an average of 2 Cmm colonies after 20 min. Further increase to 120 μg shows no significant change. However, the average colonies was observed for 48 μg after 1, 2, 12, and 24 h. The obtained results indicate that silver nanoparticles are a promising inhibitor, bactericide and high a specter antimicrobial for treatment or prevention of Cmm.